Réponses

Meilleure réponse !
2013-01-24T14:38:58+01:00

Coucou,

 

*=multiplié

Tu sais que :

(a - b)² = a² - 2*a*b + b² = a² - 2ab + b²

(a + b)²a² + 2*a*b + b² = a² + 2ab + b²

 

Maintenant, on applique la formule :

A = (6 + x)² =  6² + 2*6*x + x² = 36 + 12x + x² = x² + 12x + 36

B = (6 - x )² =  6² - 2*6*x + x²  =  36 - 12x + x²  = x² - 12x +36

 

C = (6 x  X )² =  6² x X²  = 36 x X² = 36 X²

 

D = (3 + x )² =  3² + 2*3*x + x²  = 9 + 6x + x²  = x²+ 6x + 9

E = (3 - x )² =  3² - 2*3*x + x² = ....(je pense que tu as compris, je te laisse finir)

 

F = (3 x   X ) ²=   3² x X²  = 9 X²

 

Voilà :)